2004
DOI: 10.3917/autr.030.0003
|View full text |Cite
|
Sign up to set email alerts
|

L'organisation de la mobilité dans les sociétés rurales du Sud

Abstract: Autour de Kopytoff: le débat conceptuel * Jean-Pierre Chauveau est socio-anthropologue, directeur de recherche à l'IRD (UR «Régulations foncières, politiques publiques et logiques d'acteurs»), associé à l'UMR MOISA (Montpellier) et au programme CLAIMS

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0
4

Year Published

2010
2010
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(18 citation statements)
references
References 17 publications
0
14
0
4
Order By: Relevance
“…We showed that the agricultural dynamic in the pioneer fringe in our study imbricated two distinct farming systems, where greenhouse horticulture, practised by lessees and sharecroppers, fuelled the expansion of date palm plantations of the landowners on what was previously pastoral rangeland. Bisson () analysed a similar transformation process on what can be called an internal date palm frontier (see Chauveau et al, ) in Tunisia's Nefzawa, also at the expense of pastoral rangeland. Interestingly, Bisson () also highlighted the importance of the imbrication of two distinct cropping systems in this pioneer fringe, combining alfalfa, intended for the recently settled nomadic populations and their livestock, with short‐term gains and date palms generating profit over the long term.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We showed that the agricultural dynamic in the pioneer fringe in our study imbricated two distinct farming systems, where greenhouse horticulture, practised by lessees and sharecroppers, fuelled the expansion of date palm plantations of the landowners on what was previously pastoral rangeland. Bisson () analysed a similar transformation process on what can be called an internal date palm frontier (see Chauveau et al, ) in Tunisia's Nefzawa, also at the expense of pastoral rangeland. Interestingly, Bisson () also highlighted the importance of the imbrication of two distinct cropping systems in this pioneer fringe, combining alfalfa, intended for the recently settled nomadic populations and their livestock, with short‐term gains and date palms generating profit over the long term.…”
Section: Discussionmentioning
confidence: 99%
“…Such earlier organized spaces related in North Africa's Sahara, for instance, to the pastoral rangeland exploited by nomads and which declined due to the sedentarization of nomadic populations and the regression of transhumant pastoralism (Bisson, ). Following Kopytoff's seminal work (), more recent studies, therefore, refer to an ‘ever‐renewed process of colonisation of “internal” or “interstitial” frontiers, operating on the margins of already established socio‐political entities' (Chauveau et al, ). Caron () makes a further distinction between pioneer fronts and pioneer spaces in order to distinguish between what happens at the front and the process of appropriation that takes place within the spaces.…”
Section: Introductionmentioning
confidence: 99%
“…They wrote in the introduction that: “The theme of the construction of rights and access to resources leads us in all logic to expand consideration of the issue of internal frontiers to intermediary institutions – State administrations, development agencies, markets – which take part in the contemporary government of people and territories” (Chauveau et al . , p.15). Drawing on the internal frontier thesis, this paper describes the challenges driving a complex and constantly evolving field of social, economic, and political competition.…”
Section: The Frontier Thesis: From Turner To Kopytoffmentioning
confidence: 95%
“…In the present context, the liberalisation of the mining sector has introduced an important outside actor into the space for political competition that determines access to mining resources, making the frontier thesis even more complex, since it involves, turning once more to Chauveau et al ., “combining the two frontier concepts, as meant by Turner and Kopytoff” (Chauveau et al . , p.16).…”
Section: International Junior Mining Companiesmentioning
confidence: 95%
“…Similarly, studies have been conducted on socio-cultural dynamics [53,54] in northern Benin, population pressure and agricultural development in the Adja Plateau and the marital relations and sustainable development of the Adjatado of Kufo [55,56] in southern Benin. Recent contributions [29] on rural migration, access to land and inter-ethnic relations in southern Borgou (Benin) and several other studies [4,57,58] remain important theoretical and conceptual references. This paper delves into the relationship between migration, bride prices and changing family relationships in the context of physical environmental change in the northeast of Ghana, with a case study on the Frafra in the Bongo District.…”
Section: Environmental Change and Migration: Theoretical Debatesmentioning
confidence: 99%